Impaired anti-SARS-CoV-2 antibody response in non-severe COVID-19 patients with diabetes mellitus: A preliminary report. Issue 1 (January 2021) - Pal, Rimesh; Sachdeva, Naresh; Mukherjee, Soham; Suri, Vikas; Zohmangaihi, Deepy; Ram, Sant; Puri, Goverdhan Dutt; Bhalla, Ashish; Soni, Shiv Lal; Pandey, Navin; Bhansali, Anil; Bhadada, Sanjay Kumar
Abstract: Background and aims: Patients with diabetes mellitus (DM) often demonstrate impaired antibody response to influenza/hepatitis B vaccines. Hence, we compared anti-SARS-CoV-2 antibody response in non-severe COVID-19 patients with and without type 2 diabetes mellitus (T2DM). Methods: Records of non-severe COVID-19 patients admitted at our institution between April 10, 2020 and May 20, 2020 were retrieved. Qualitative detection of total (IgG + IgM) anti-SARS-CoV-2 antibody was performed using electrochemiluminescence immunoassay in plasma samples collected at least 14 days post-polymerase chain reaction (PCR) confirmation of diagnosis. Results: Thirty-one non-severe COVID-19 patients were included. Nine patients (29%) had T2DM with mean HbA1c at admission of 8.3 ± 1.0%. Anti-SARS-CoV-2 antibody was estimated at a median of 16 (14–17) days post-PCR confirmation of COVID-19 diagnosis. Only three patients (10%) were seronegative, and all had T2DM. Patients with T2DM were more likely to have non-detectable anti-SARS-CoV-2 antibodies than those without DM ( p = 0.019). Conclusions: COVID-19 patients with T2DM may not undergo seroconversion even after two weeks of diagnosis. Impaired seroconversion could theoretically increase the risk of reinfections in patients with DM. However, the finding requires validation in large-scale studies involving serial estimations of anti-SARS-CoV-2 antibodies in patients with and without DM. Highlights: Non-severe COVID-19 patients with T2DM were more likely to be seronegative for anti-SARS-CoV-2 antibodies. Seronegative patients had higher HbA1c and longer duration of T2DM than seropositive patients. Absence of anti-SARS-CoV-2 antibodies might increase the risk of reinfections in patients with T2DM.